Efek Pemberian Temu Putih (Curcuma zedoaria) terhadap Kualitas Susu Sapi Perah Penderita Mastitis Subklinis - E Nurdin; H Susanty (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
An experiment was conducted to evaluate the effect of Curcuma Zedoaria on milk composition of sub-clinical mastitis dairy cow. Concentrate was prepared by mixing level of curcuma zedoaria powder. Nine heads of sub-clinical mastitis dairy cows were divided into three groups. The first group were as a control, the second group were treated with 0.02% of Curcuma zedoaria according to body weight , and likewise the third group were treated 0.04% of Curcuma zedoaria. Data were analyzed with Variance analysis in a completely randomized design. The result showed that there were no significant effect of using different levels of Curcuma Zeoaria. The quality of milk in term of fat, protein, dry matter were satisfied for the quality standard of milk.